Asuhan Keperawatan Jiwa pada Ny.S dengan Masalah Utama Gangguan Persepsi Sensori: Halusinasi Pendengaran Akibat Skizofrenia Paranoid di Ruang Dewaruci RSJD dr. Amino Gondohutomo Provinsi Jawa Tengah - Icha Lulita; Titi Sri Suyanti; Tati Karyawati (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
Mental health is the realization of harmonious mental functions, which allows one to face challenges, feel happy, and feel capable. A healthy soul includes self-actualization, a positive attitude towards oneself, progress, and a realistic perception of adaptation (Oktaviani & Apriliyani, 2022). Hallucinations refer to phenomena when individuals experience sensory changes in response to stimuli that are objectively absent (Refnandes et al., 2023). The purpose of this paper is to determine and provide mental nursing care to Mrs. S with the main problem of sensory perception disorders: auditory hallucinations due to paranoid schizophrenia in the Dewaruci ward of dr. Amino Gondohutomo Mental Hospital, Central Java Province in accordance with nursing standards. The method used is a descriptive method in the form of interviews, observations, documentation studies, literature studies and literature. From the case review, it was found that the patient’s main complaint said “I heard a whisper telling me to leave the house, sis”. There are 4 nursing problems, namely the risk of violent behavior, sensory perception disorders: auditory hallucinations, social isolation and self-care deficits. Interventions are designed based on TUM and TUK and on the client’s condition and can be implemented.